Mood states of active and insufficiently active adolescents related to sleep quality, gender, academic performance and guidelines for the post-COVID-19 scenario - Andrade, Alexandro; D’Oliveira, Anderson; dos Santos, Keyla Mara; Falese, Lavinia; Mancone, Stefania; Diotaiuti, Pierluigi; Stabile, Luca; Buonanno, Giorgio (Frontiers in Psychology, 2024)
Objective: To evaluate the impact of physical activity on the mood states of active and insufficiently active Italian adolescents and the relationships with sleep quality, sex, and academic performance, analyzing guidelines for the post-COVID-19 scenario. Methods: This is a cross-sectional, quantitative, and descriptive study. Data collection was carried out through an electronic questionnaire via Google Forms. Adolescent students from schools in the Lazio region, Italy, were evaluated. Results: In total, 437 Italian adolescents were included, with a mean age of 15.9 ± 1.37 years. The average time of exercise reported by the students was 277 minutes per week. Physical activity appears to be positively correlated with improved mood states, particularly in adolescents who engage in 150 minutes or more of physical activity per week, who exhibited notably higher levels of vigor. It was found that female adolescents presented a worse mood state, greater tension, depression, anger, fatigue, and mental confusion, and worse vigor when compared to boys and that adolescents who had poor sleep quality presented significantly worse mood state. Adolescents with an insufficient perception of academic performance demonstrated a significantly worse mood state, tension, depression, anger, and mental confusion, with a submerged mood profile when compared to adolescents who perceived themselves as excellent, with an iceberg profile. In the regression analysis, it was found that for each minute of physical activity practiced, the score in the state of vigor of the adolescents increased by 0.02 and mental confusion decreased by 0.002. Conclusion:From the present findings, we conclude that recommendations on PA practices for adolescents should be strengthened, as a way to mitigate possible damage to mood states, especially in the post-COVID-19 scenario. Future studies need to deepen the relationships between the mental health, sex, and academic performance of adolescents to strengthen positive mood states and elucidate information on the type, intensity, and dosage of physical activity to achieve mood benefits.